KH. NOER ALIE IS A MULTI-DIMENSIONAL CLERICAL FIGURE AND HIS WORK IN SOCIETY - Kholilullah Ahmas (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
Research on the figure of KH. Noer Alie as a multi-dimensional scholar, is felt to be so important for academics, da'ie, educators and the wider community. This is because K.H. Noer Ali is a scholar, preacher, and fighter who was directly involved in confrontations with Dutch and Japanese colonizers during the revolutionary period and then took part in the community in the fields of da'wah, education and society in the post-revolutionary era. From the continuous struggle that is considered to be a major contribution to the existence of the Unitary State of the Republic of Indonesia (NKRI), finally the Indonesian Government has conferred the title of national hero to K.H. Noer Ali for his services for Indonesian independence. The objectives of the study are; first; to analyze the concepts of thought, approaches and methods of K.H. Noer Ali in various gait which include politics, education, da'wah and social in society, second; to find out the implementation of the concepts, approaches and methods of K.H. Noer Ali's gait in society . This research uses a qualitative approach with library research sources, library research is research that reveals facts or data in research obtained through books, journals and other scientific works related to the object of research. This research uses several types of methods, including; description, historical and sociological methods. From some literature, it was found that KH Noer Alie is a cleric who is dubbed as a multi-dimensional cleric figure, this is based on his extensive role and work in the community covering various aspects of life. In addition to being a cleric figure, KH. Noer Alie is also known as a warrior figure, da'ie figure, educator figure, political figure, organizational figure and community figure. The results of this study indicate that the concept of K.H. Noer Alie's work comes from the Qur'an and Hadith as the main source of Ahlu Sunnah waljama'ah Islam, this concept emphasizes strengthening a good understanding of Islamic teachings based on these two sources. In taking part, the approach taken by K.H Noer Alie is through political, educational, da'wah and social struggles, the methods used are exemplary methods, deep attention and direct interaction with the community.